Dancimagem: por uma relação quinhoeira no ensino e na dança - CARVALHO, Claudio Leandro Barbosa (2021)
This work aims to contribute with the knowledge produced in dance that deals with the relationship between teaching and learning in the school context, evidencing a way of seeing / reading / expressing / being in the world, reflecting the interaction between students and teacher of dance through a humanized relationship, where the hierarchy is clarified to what concerns the classroom. It also aims to propose reflections for a healthy socialization between student and teacher through the use of dance and image as ways of triggering teaching and learning. In order to understand and unfold the present research object, some theorists have been adopted to contribute to the composition of the thought that is here, so that, as scribbles at the beginning of a painting, they could serve as references to all covered approaches, among the which I emphasize some dance concepts pointed out by Adrienne Kaeppler (2013) and Paul Valéry (2012); and the questions about image presented by the studies of Paul Valéry (2012). In the teaching and learning of dance, I write about Isabel Marques and Fabio Brazil (2014), which point out important issues for the teaching of the arts in schools, and dialogue with Adriana Friedmann (2013) in her studies on multicultural manifestations of the infant universe.